PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA CV RAKASINDO MEGATAMA DI SEMARANG - Ocky Hermawan, 10.05.51.0153; Murdiyanto, Agus (Students Journal of Economic and Management, 2014)
The purpose ofthis study wastodetermine the effect ofa positiveand significant correlation betweenleadershipandmotivation givento employee performanceCVRakasindoMegatamainSemarang. The populationinthis study were allemployees inCVRakasindoMegatamatotaling75employees, then itdeservestobe sampledwithout having totakethe samplein acertainamount. Thus, the samplesofthis studywere all employees oftheCVRakasindoMegatama. The analytical toolusedin this studyismultiple linear regression. The results showedthat theleadershiphave a significant effecton employee performance. This canbe interpretedif theleadershipof employeesincreases,increasedemployee performance. Motivationsignificant effect onemployee performance.This canbe interpretedif themotivationincreases,increasedemployee performance. Keywords: leadership, work motivationandperformance ofemployees